PERFORMANCE OF SERIES CIRCUIT CONFIGURATION ON PIEZOELECTRIC SENSORS COATED WITH Zn-DOPED CARBON DOTS AS ENERGY GENERATING SPEEDBUMPS - Fauziyah Vida Rahmah Wijaya; Akbar Sujiwa; Nur Aini Fauziyah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
The increasing demand for electrical energy has driven the exploration of alternative energy sources. The mechanical energy generated by vehicles passing over speed bumps can be harvested on a small scale using piezoelectric sensors. This study investigates the performance enhancement of piezoelectric elements coated with Zn-doped Carbon Dots (CDs) and their application in a series-configured energy- harvesting speedbump. Zn-doped CDs were synthesized using the sol-gel method, and the materials were characterized by XRD, SEM, EDX, and mechanical testing of the piezoelectric sensors under varying loads. XRD characterization indicates that the commercial piezoelectric material contains BaTiO3 as the primary phase and BaO as the secondary phase. SEM EDX analysis confirms that the particle size distribution of Zn-doped CDs ranges from 0 to 2400 nm. Single-element testing of the PLRCZ layer shows that the piezoelectric sensor with a resin/Zn-doped CDs coating generates a higher voltage compared to the uncoated sensor under a load of 122.8 g. In the series configuration, the output voltage decreases at each load point, reaching a maximum of 1 V, while across all PLRCZ elements, the voltage reaches a maximum of 0.4 V, with no detectable current.